POST TRAUMATIC STRESS DISORDER AS ONE OF EMERGING PSYCHIATRIC CONSEQUENCES OF COVID-19 - Ahmed, Hafiz Shafique; Leghari, Naeem Ullah; Iqbal, Khizra; Kreem, Owais; Jahan, Musarrat; Dastgeer, Saima (Journal of Pakistan Psychiatric Society, 2023)
Objective: In this study, we aimed to determine the associated factors in prevalence of PTSD among patients with COVID-19 who were treated.Study Design: Cross-sectional studyPlace and duration of the study: the study was conducted in medical OPD of DG khan from August, 2021 to December, 2021.Subjects and method:  120 PTSD patients were approached through convenient sampling technique. PCL-5 scale was used to assess severity of PTSD symptoms. SPSS-22 was used to analyse the data.Results: showed the severity of PTSD symptoms, in the patients re-experiencing symptoms were quite a bit  31.7%, avoidance were extreme 30%, symptoms of negative alteration in cognition and mood were moderate 37.5% in most of the patients and hyperarousal was quite a bit severe 37.5% in most of the patients. Conclusionsthe findings confirm that PTSD symptoms were moderate to severe including the re-experiencing, avoidance, alteration in mood and cognition and hyperarousal in most of the participants who were exposed to COVID-19 symptoms.  There should be some preventive measures and interventions to overcome and protect individuals from PTSD symptoms.Key Words: COVID-19, Post-traumatic Stress Disorder, Eye witnessed